Comparison of Virtual Reality-Based Rehabilitation and High-Intensity Exercise After Total Knee Arthroplasty: A Randomized Controlled Trial - S. Parekh, Saloni; Khan, Jafar; Pal, Renuka; Sharma, Deepak; Annamalai, K.M.; Pinjara, Farukh Mohammad; Qureshi, Abid R; Jain, Preksha; Kania, Vaishnavi; Bhatnagar, Suhani (Journal of Neonatal Surgery, 2025)
Objective: To determine whether VR-based rehabilitation (VRBR) reduces pain and improve balance, proprioception and joint function following Total knee replacement (TKR). Methods: The randomized controlled trials (RCTs) were included if they were in English, participants aged ≥ 18 years, underwent a unilateral or bilateral TKR and were treated using VRBR. The outcome was measured Berg balance scale (BBS) and Timed Up and Go Test. Results: The data was found to be normally distributed. Virtual reality training group shows better effects as compared to conventional balance training group in terms of BBS (p<0.001) and TUG-test (p<0.001). Conclusion: The range of motion in VR-based rehabilitation produces better results than indifferently supporting the experimental group's pain outcome, but the VRBR showed significant improvement.